2017
DOI: 10.1002/acm2.12229
|View full text |Cite
|
Sign up to set email alerts
|

On the use of bolus for pacemaker dose measurement and reduction in radiation therapy

Abstract: Special attention is required in planning and administering radiation therapy to patients with cardiac implantable electronic devices (CIEDs), such as pacemaker and defibrillator. The range of dose to CIEDs that can induce malfunction is large among CIEDs. Clinically significant defects have been reported at dose as low as 0.15 Gy. Therefore, accurate estimation of dose to CIED and dose reduction are both important even if the dose is expected to be less than the often‐used 2‐Gy limit. We investigated the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…If the device sits within 5 cm proximal to the field edge, a bolus (1-2 cm thickness) on the top of the device for the entire course of treatment minimizes scatter and leakage because the photon spectra outside the treatment fields are in the kV range. 14 , 44 Chan et al reported that placement of bolus on the top of the ICD would reduce the dose to the device by 34% to 58% depending on the distance from the edge of the field. 14 Treatment planning techniques such as coplanar beam arrangement can also reduce entry and exit through the device.…”
Section: Management Of Commonly Seen Implanted Devices In Rt Patientsmentioning
confidence: 99%
“…If the device sits within 5 cm proximal to the field edge, a bolus (1-2 cm thickness) on the top of the device for the entire course of treatment minimizes scatter and leakage because the photon spectra outside the treatment fields are in the kV range. 14 , 44 Chan et al reported that placement of bolus on the top of the ICD would reduce the dose to the device by 34% to 58% depending on the distance from the edge of the field. 14 Treatment planning techniques such as coplanar beam arrangement can also reduce entry and exit through the device.…”
Section: Management Of Commonly Seen Implanted Devices In Rt Patientsmentioning
confidence: 99%
“…Consequently, the survival probability for patients to live enough for experimenting with late radiation effects has progressively increased [1]. So, knowing the peripheral (outside the field edge) low absorbed dose received by healthy surrounding organs becomes an important issue [2][3][4], principally if anatomical structures with tolerances to low absorbed dose are involved. From a biological standpoint, it is well known that for a given absorbed dose value, the radiobiological effect varies with the energy beams.…”
Section: Introductionmentioning
confidence: 99%
“…They are widely used in radiotherapy to alter the dose distribution of ionising radiation, especially during irradiation of superficial neoplastic lesions. Boluses provide additional absorption and scattering of ionising radiation, resulting in a more homogenous dose delivered to the area being treated (Hogstrom and Almond 2006 ; Łukowiak et al 2017 , 2016 ; Yan et al 2018 ; Stone et al 2003 ; Khan 2003 ).…”
Section: Introductionmentioning
confidence: 99%